2022
DOI: 10.18632/aging.204070
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin 3 depletion (PTX3 KD) inhibited myocardial fibrosis in heart failure after myocardial infarction

Abstract: Background: HF is a common complication of MI. The underlying mechanisms of myocardial fibrosis in HF after MI are incompletely defined. Here, this study aims to investigate the role of PTX3 KD in HF after MI. Methods: Bioinformatics analysis based on GSE86569 dataset was performed to explore the potential role of PTX3 in HF. Male C57/BL6J mice were administered with lentiviral vector encoding PTX3 KD or empty vector, and then underwent either coronary ligation or sham surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These findings reveal MF is associated with collagen metabolism and contributes in the mechanism of AF. The clinical data showed that many factors are associated with the process of MF, such as oxidative stress, calcium overload, inflammation, and the activation of myofibroblasts [1][2][3]. In normal conditions, the body can produce antioxidant enzymes such as SOD to remove excess ROS and keep the level of free radicals in the body at a steady state [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings reveal MF is associated with collagen metabolism and contributes in the mechanism of AF. The clinical data showed that many factors are associated with the process of MF, such as oxidative stress, calcium overload, inflammation, and the activation of myofibroblasts [1][2][3]. In normal conditions, the body can produce antioxidant enzymes such as SOD to remove excess ROS and keep the level of free radicals in the body at a steady state [23].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent atrial fibrillation (AF) can lead to electrical and structural remodeling, and myocardial fibrosis (MF) is an important feature of structural remodeling. Available experimental and clinical data suggest that there are many factors involving in the development of MF and AF, such as calcium overload, inflammation, oxidative stress, and activation of myofibroblasts [1][2][3]. MF is an important pathological feature of AF, resulting in the excessive deposition of the extracellular matrix, causing myocardial remodeling and even heart failure (HF) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, There are many other drugs that can improve fibrosis, such as piperine, thymoquinone, an oleanolic acid Qi-Tai-Suan, spinal cord stimulation and exogenous hydrogen sulfide ( Li et al, 2020f ; Viswanadha et al, 2020 ; Farag et al, 2021 ; Qian et al, 2022 ; He et al, 2023 ). Endostatin, alarin, L-carnitine, pentraxin 3 depletion, and mdivi-1 also can attenuate oxidative stress to inhibit myocardial fibrosis ( Li et al, 2021b ; Xu et al, 2021b ; Emran et al, 2021 ; Xu et al, 2022a ; Ding et al, 2022 ).…”
Section: Interventions For Cardiac Fibrosismentioning
confidence: 99%